WHO NEEDS CULTURAL INTERMEDIARIES? - Nixon, Sean; Gay, Paul Du (Cultural studies (London, England), 2002)
Introduces the topic of "cultural intermediaries," with particular reference to the work of Pierre Bourdieu. Cultural intermediaries here refer to occupational groups & the terminology devised to categorize & conceptualize their social roles & participation in the occupational division of labor. For Bourdieu, these are workers engaged in providing symbolic goods & services. Their significance in consumer & media sectors is as cultural intermediaries with a degree of cultural authority vis-a-vis taste & buyers' preferences but this role also places them in conflict with the realm of traditional intellectuals. The problems of terminology, periodization, empirical grounding, & strategic value that remain under debate for analysts of cultural intermediaries are addressed by the issue's contributors. 12 References.